The effects of neem oil (Azadirachta indica A. JUSS) enriched with different concentrations of azadirachtin on the integument of semi-engorged Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) females - Lima de Souza, José Ribamar [UNESP]; Remedio, Rafael Neodini [UNESP]; Arnosti, André [UNESP]; de Abreu, Rusleyd Maria Magalhães [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Wiley, 2017)
Several studies searching for methods to control Rhipicephalus sanguineus s.l., (dog tick) infestations have been developed aiming to minimize the damages caused by these ectoparasites to the hosts and the environment, which is harmed by the indiscriminate use of toxic acaricide products. In this scenario, neem oil has been used as a natural alternative against ticks, once this chemical has repellent properties and interferes in the growth regulation of these ectoparasites, inhibiting ecdysis. The present study evaluated the effects of azadirachtin-enriched neem oil on the integument of semi-engorged R.sanguineus s.l., females through morphohistological techniques. The results showed the occurrence of significant morphological and histochemical alterations, mainly in the females exposed to higher concentrations, which demonstrates the dose-dependent action of the chemical. A decrease in the cuticle thickness was observed, as well as a modification in the distribution of the epithelial cells, which displayed pyknotic and fragmented nuclei, and intensely vacuolated cytoplasm, indicating that these cells would be undergoing death processes. These morphological alterations observed in the integument of the females exposed to the azadirachtin-enriched neem oil encourage the use of this chemical as a strategy to control these ectoparasites.
Keywords: acaricide; control; cuticle; histochemical; morphohistological